Pengaruh Program Ma'arif Mart terhadap Edupreneur Peserta Didik di MTs Darul Ulum Waru Sidoarjo - Ismawati, Putri; Aisida, Sufinatin (ISLAMIKA, 2024)
The modern canteen located at the school or commonly called ma'arif mart which is under the auspices of LP Ma'arif NU, is a modern shop or canteen that serves the basic needs of school residents directly. The existence of businesses in the field of education such as ma'arif mart can provide learning to students for entrepreneurship. Edupreneur is a structured and formal process of transmitting entrepreneurial competencies that refers to the provision of conceptual skills and individual mental awareness. The purpose of this research is to: (1) Explain the Ma'arif Mart Program at MTs Darul Ulum Waru Sidoarjo. (2) Explaining Student Edupreneurs at MTs Darul Ulum Waru Sidoarjo. (3) Explaining the Effect of the Ma'arif Mart Program on Student Edupreneurs at MTs Darul Ulum Waru Sidoarjo. This research is a type of descriptive quantitative research. The subjects of this study were all students of MTs Darul Ulum Waru Sidoarjo whose population totaled 857 students and the sample used a stratified technique which totaled 85 students. The instrument used for data collection is the questionnaire instrument. The results of the study show that, (1) That the Ma'arif Mart Program at MTs Darul Ulum Waru Sidoarjo is categorized as "Good Enough". This is based on percentage calculations with a value of 70.03%, according to the standard percentage at intervals of 56% to 75%. (2) Edupreneur students at MTs Darul Ulum Waru Sidoarjo have developed which are categorized as "Good". With the results of the percentage analysis of 76.62% which is in the interval between 56% to 75%. (3) The results of data analysis rxy = 0.521 show that "There is an Influence of the Ma'arif Mart Program on Student Edupreneurs at MTs Darul Ulum Waru Sidoarjo". This is evidenced by the analysis carried out using the "r" product moment table, the rxy price is 0.521 and the rxy value from the interpretation table is between 0.40 and 0.599 in a fairly strong category.